Intangible assets and their impact on economic performance - Bavdaž, Mojca (Economic and business review, 2022)
The paper introduces the topic of intangible assets. It describes the evolution of the concept of intangible assets and the role of these assets in today’s economy. The importance of intangible assets is highlighted through many quantitative estimates of the impact that intangible assets have on economic performance. After reviewing research carried out mainly in the Western economies, the paper concentrates on the research covering the size and impact of intangible investment in the Central and Eastern European (CEE) and Balkan countries. Moreover, the focus shifts to the firm level where the management of intangible assets faces several challenges that range from identification and valuation of intangible assets to leadership of knowledge-intensive firms. Progress at all levels is to some extent hampered by the lack of adequate data, which should be addressed by establishing a standard definition and ensuring more data on intangibles within financial reporting. Bold steps should therefore be made towards better measurement of intangible investment and better use of this source of productivity growth.
Keywords: Balkan; Central and Eastern Europe; economic growth; ekonomska rast; intangible assets; nematerialne naložbe; productivity; produktivnost; srednja in vzhodna Evropa; the Balkans